IDDF2022-ABS-0195 Tumor cells-derived lipids modulate macrophage activity to regulate immunotherapy resistance of hepatocellular carcinoma. (2nd September 2022) - Liang, Zhixian; Cao, Jianquan; Tang, Wenshu; Wu, Haoran; Tu, Yalin; Xiong, Zhewen; Zhou, Jingying; Chan, Stephen L; Cheng, Alfred SL
Abstract : Background: Immune-checkpoint blockade (ICB) therapies have transformed the treatment landscapes of hepatocellular carcinoma (HCC). Despite unprecedented success in clinical trials, the immunosuppressive tumor microenvironment (TME) constructed by tumor cells restricts the responsiveness of ICB therapies to a minority of patients. Triggering receptor expressed on myeloid cells-2 (TREM2) counteracts inflammation and maintains metabolic fitness in myeloid cells. Emerging single-cell RNA sequencing (scRNA-seq) data in different types of tumors have identified the significance of TREM2 + myeloid cells in tumor development and ICB resistance. In this study, we aimed to investigate the potential role of TREM2 in HCC ICB resistance and to identify intrinsic regulators within the TME that promote TREM2 expression and function. Methods: We conducted scRNA-seq of tumor biopsies in a phase II clinical trial of pembrolizumab (anti-PD1) on advanced HBV-related HCC patients (NCT03419481 ) to delineate the distinct myeloid landscape of the TME between ICB-responsive and non-responsive HCC. Two syngeneic ICB-resistant and sensitive HCC mouse models were used to validate the clinical findings and explore the potential role of TREM2 involved in HCC ICB resistance. Bone marrow-derived macrophage was used to explore the regulation of tumor cells on myeloid Trem2 expression. Furthermore, we constructed myeloid cell targeting short-hairpin RNA (shRNA) lentiviruses against Trem2 (shTrem2) to down-regulate Trem2 in vitro and in vivo. Results: scRNA-seq analysis of our pembrolizumab trial on advanced HCC identified a subset of tumor-associated macrophages over-expressing TREM2 in non-responders. Consistently, our syngeneic ICB-resistant HCC mouse models verified a group of Trem2 + myeloid cells, which were accumulated in the lipid-rich TME of ICB-resistant tumors. Compared to the parental ICB-sensitive tumor cells, the conditional medium (CM) of ICB-resistant tumor cells significantly increased Trem2 expression in macrophages, which was abolished when lipids in the CM were depleted. Notably, lentivirus-mediated Trem2 ablation reduced lipid accumulation in TME and overcame anti-PD-1 resistance with increased cytotoxic CD8 + T cell infiltration. Conclusions: Our study highlights TREM2 as an immuno-metabolic target to enhance HCC immunotherapy.